ANALYSIS OF STUDENTS’ MOTIVATION IN CHOOSING ENGLISH PROGRAM AT IAIN PAREPARE - Erniati Burhan; Mujahidah Mujahidah; Magdahalena Tjalla (Journal of English Education, 2025)
This study aims to describe students' motivation in choosing an English Program at IAIN Parepare. Motivation has an important influence on learning outcomes that will help students get jobs that match their expectations and desires. This encourages students to be more selective in choosing study programs because it will affect their future of the students. The type of research used is descriptive qualitative research design in the form of qualitative content analysis. Researchers collected data using observation and interview methods. Data analysis was obtained from interview results. Respondents to this study were 20 PBI students, 5 from each odd semester class. the difference between this research is that previous research used quantitative research with questionnaires as a data collection method, while this study used qualitative methods in which data were collected through an interview process. The results of this study indicate that each student has more than one factor that influences or motivates them in choosing the English Program. Major selection factor found in this study is a source of information and influence, job characteristics, financial considerations, suitability and interest, psychological or social benefits, characteristics of majors, and feeling challenged. The most common responses regarding the factors influencing students in choosing an English Program in this study were suitability and interest.